2015
DOI: 10.1111/ijfs.12922
|View full text |Cite
|
Sign up to set email alerts
|

Effect of germination on vitamin C, phenolic compounds and antioxidant activity in flaxseed (Linum usitatissimum L.)

Abstract: Summary Flaxseed (Linum usitatissimum L.) is well known for its health benefits and chemical composition. This study aimed to evaluate the dynamic changes caused by germination in vitamin C, phenolic compounds and antioxidant activities of flaxseed. It was observed that eight‐day germination of flaxseed sprouts caused increases in phytochemical contents, that is 22.1‐fold increase in vitamin C, 2.67‐fold increase in phenolics and 5.48‐fold increase in flavonoid contents as compare to initial concentration in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 37 publications
8
31
1
Order By: Relevance
“…Long‐term germination may have a negative effect on SDG content. It has been found that flaxseeds have the highest SDG content on the eighth day of 10‐day germination (Wang et al ., 2016a), which is similar to the trend of SDG content in this study. The increasing in the SDG could be due to the de novo synthesis of lignan during germination, and this result is also in line with our expectations.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Long‐term germination may have a negative effect on SDG content. It has been found that flaxseeds have the highest SDG content on the eighth day of 10‐day germination (Wang et al ., 2016a), which is similar to the trend of SDG content in this study. The increasing in the SDG could be due to the de novo synthesis of lignan during germination, and this result is also in line with our expectations.…”
Section: Resultssupporting
confidence: 89%
“…Seeds were washed twice a day to avoid microbial growth, collected every day and measured for the changes in root length during 5‐day germination. The collected samples were lyophilised, milled and passed through a sieve of 0.5 mm, stored at −20 °C (Wang et al ., ,b). The moisture content was determined by oven‐dried method (Wolfe & Liu, ) with modification.…”
Section: Methodsmentioning
confidence: 99%
“…Recently phenolic components in flaxseed have attracted an increasing attention (Wang et al, ). The identification and quantification of phenolic compounds in flaxseed was conducted with the use of UPLC system and the respective results are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant potential of flaxseed protein or protein hydrolysates in prevention of lipid oxidation in food products has been demonstrated (Hwang, Chen, Luo, & Chiang, ). Wang et al () evaluated changes caused by germination on phenolic compounds and antioxidant activities of flaxseed. A review of the scientific literature with regard to flaxseed indicates that extensive studies have been undertaken to demonstrate the antioxidant potential of flaxseed and their phenolics but there are no published papers on quantification of phenolic compounds in flaxseed by UPLC as influenced by heat‐processing methods.…”
Section: Introductionmentioning
confidence: 99%
“…We can come to a conclusion that 10-15 DAP and 25-30 DAP are two essential stages in sweetcorn for kernels to accumulate massive carotenoids. At the same time, feedback inhibition also exists in carotenoid biosynthesis (Wang et al, 2015). In YT16, high expression level of Zm CRTISO led to high level of carotenoid accumulation.…”
Section: Changes Of Carotenoid Profiles In Sweetcorn During Kernel Dementioning
confidence: 98%